1928
DOI: 10.1017/s0025315400055703
|View full text |Cite
|
Sign up to set email alerts
|

The Photosynthesis of Diatom Cultures in the Sea

Abstract: With 24 Figures in the Text.PHOTOSYNTHESIS in the opensea is duemainly to two groupsoforganisms, the diatoms and the dinoflagellates. In British seas the diatoms are so much more numerous that the chemical changes which are due to photosynthetic activity can be almost entirely ascribed to their influence. Recent work on these chemical chang.es has shown that they do not ,extend deeper than about 30 metres. Of the external limiting factors light is among the most important and the depth to which photosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

1930
1930
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 3 publications
3
29
1
Order By: Relevance
“…7, with the oxygen as ordinates, and the time of day as abscissae, for the various depths. The relation of the oxygen production to the waxing and waning of daylight is clearly shown, as well as the midday inhibition near the surface; this result is closely similar to that obtained by Marshall & Orr (1928, fig. 7, p. 328) for a sunny summer day in the Clyde.…”
Section: Night Exposure Insupporting
confidence: 87%
“…7, with the oxygen as ordinates, and the time of day as abscissae, for the various depths. The relation of the oxygen production to the waxing and waning of daylight is clearly shown, as well as the midday inhibition near the surface; this result is closely similar to that obtained by Marshall & Orr (1928, fig. 7, p. 328) for a sunny summer day in the Clyde.…”
Section: Night Exposure Insupporting
confidence: 87%
“…The only conclusion we could draw from this finding was that production had caused the observed distribution in biomass. A winter production was already postulated long ago by Marshall & Orr (1928). Viability tests showing high F DCMU :F ratios confirmed that algae were indeed actively photosynthesising (Roy & Legendre 1979).…”
Section: Winter Production Supported By Convectionmentioning
confidence: 64%
“…28), showing the same general trend in every case of a linear increase of photosynthesis with light intensity up to a saturation point, beyond which higher intensities do not increase photosynthesis but eventually result in an inhibition, the physiology of which is discussed by Steemann Nielsen (1952). The majority of laboratory studies with terrestrial or freshwater plants have not been concerned with the high intensities at which this inhibition occurs, but the phenomenon has been clearly demonstrated in all measurements of photosynthesis in natural waters by a marked depression at or near the surface where the organisms are exposed to nearly full incident solar radiation (Marshall and Orr 1928, Jenkin 1937, Steemann Nielsen 1951, 1952.…”
Section: Althoughmentioning
confidence: 99%